Penerjemahan Kalimat Idiomatis dalam Al-Qur'an: Studi Atas Al-Qur’an dan Terjemahannya Kementerian Agama Republik Indonesia Edisi Penyempurnaan 2019 - Nadhifah, Difa (Lajnah Pentashihan Mushaf Al-Qur'an, 2023)
The main focus of this research is the translation of idiomatic verses in the Qur'an. The primary source is Al-Qur’an dan Terjemahannya (the Qur’an and its translation) by the Ministry of Religious Affairs of the Republic of Indonesia, 2019 refinement edition. The formulated questions are: 1) How is the method used in translating idiomatic verses in the Al-Qur’an dan Terjemahannya? 2) How is the quality of the translation of idiomatic verses in in the Al-Qur’an dan Terjemahannya? This research is a translation study. In terms of orientation, this research belongs to the field of productoriented translation. Two conclusions are drawn from this study. First, the translation method used for the idiomatic verses in the Qur’an is predominantly oriented towards domestication. This is evident from the translation procedure that employs the transposition procedure, serving as an indicator of the orientation used. Second, in terms of eight equivalence aspects, the quality of translation equivalence does not reach total equivalence. Nevertheless, many aspects are equivalent, particularly in the translation of idiomatic sentences oriented towards the target language.